2008
DOI: 10.1074/mcp.m800020-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

CrossSearch, a User-friendly Search Engine for Detecting Chemically Cross-linked Peptides in Conjugated Proteins

Abstract: Chemical cross-linking and high resolution MS have been integrated successfully to capture protein interactions and provide low resolution structural data for proteins that are refractive to analyses by NMR or crystallography. Despite the versatility of these combined techniques, the array of products that is generated from the cross-linking and proteolytic digestion of proteins is immense and generally requires the use of labeling strategies and/or data base search algorithms to distinguish actual cross-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
(47 reference statements)
1
29
0
1
Order By: Relevance
“…We assume that cross-linking of the ␤ subunit in the intact complex captures a conformation of this subunit that is induced by its interactions with all subunits, including itself, in the 4°structure of PhK. In further support of the use of this cross-linking constraint, we recently demonstrated that PhK binds the glucoamylase inhibitor acarbose and that this binding perturbs intramolecular cross-linking of the ␤ subunit by GMBS (64), which cross-links the GHL domain to the C terminus of the ␤ subunit (30). The direct binding of acarbose by the ␤ GHL domains would allow a potential mechanism for inducing a conformational change in this subunit through altering potential interactions between the predicted ␤ GHL and the HRL domains, consistent with results from the intramolecular cross-linking of ␤ by DFDNB.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…We assume that cross-linking of the ␤ subunit in the intact complex captures a conformation of this subunit that is induced by its interactions with all subunits, including itself, in the 4°structure of PhK. In further support of the use of this cross-linking constraint, we recently demonstrated that PhK binds the glucoamylase inhibitor acarbose and that this binding perturbs intramolecular cross-linking of the ␤ subunit by GMBS (64), which cross-links the GHL domain to the C terminus of the ␤ subunit (30). The direct binding of acarbose by the ␤ GHL domains would allow a potential mechanism for inducing a conformational change in this subunit through altering potential interactions between the predicted ␤ GHL and the HRL domains, consistent with results from the intramolecular cross-linking of ␤ by DFDNB.…”
Section: Discussionmentioning
confidence: 93%
“…The corresponding log file was used to generate a list of parent ions for which the corresponding charges and tandem mass spectra were obtained. A list of potential conjugates was generated from the resulting mass list ((M ϩ H) ϩ ) by previously described methods (30), and the fragmentation patterns of all viable candidates were analyzed for consistency with the predicted chemistry of cross-linking (30).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations